PENDIDIKAN KESEHATAN REPRODUKSI PADA REMAJA - Belet Lydia Ingrit; Christie Lidya Rumerung; Dwi Yulianto Nugroho; Komilie Situmorang; Maria Maxmila Yoche A; Marisa Junianti Manik (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
Adolescence is a transition from childhood to adulthood that involves changes in physical and psychological aspects. Keeping healthy reproductive is very important, especially for adolescents, Lack of education on reproductive health will trigger health problems like pregnancy at a young age and abortion in adolescent girls. This community service activity is to increase adolescent knowledge about the growth and development of adolescents in general and also to increase knowledge about reproductive health for boys and girls with the health education method and also using the pretest, post-test, online reproductive health education, and question-and-answer method with a total of 118 teenagers attending. The results from this activity from the pretest and posttest showed an increase in the change in value seen from the pretest and posttest scores by 10 points, from a value of 80 to 90. The increasing score indicates the increasing cognitive abilities of participants and they understand the topic given. This Community Service went smoothly starting from preparation, during the webinar, and during questions and answer sessions. At the end of the activity, participants can explain again the information that had been given by the Community Service team such as the stages of adolescent development and growth, and knowing the health reproduction in adolescents. Furthermore, hopes that this Community Service activity can be sustainable by taking up new topics related to reproductive health in couples of childbearing age.